The Impact of Problem Based Learning with Mind Mapping on Learning Outcomes in Ecosystem Lesson - Mohammad Jamhari; Yulia Windarsih; Manap Trianto (Postgraduate, University of Mataram, 2025)
Education plays a critical role in shaping the cognitive, affective, and psychomotor development of students. In the 21st century, students are expected not only to acquire knowledge but also to develop the ability to think critically, solve problems, and apply concepts in real-life situations. For this reason, this study aims to determine the effect of applying the problem-based learning model assisted by mind mapping on student learning outcomes in ecosystem lesson. This research employed a quasi-experimental approach using the Pretest-Posttest Non-Equivalent Control Group Design, involving both control and experimental classes. The study population included all tenth-grade students at SMA Negeri 1 Biau. Through purposive sampling, four classes were selected, totaling 121 students. Learning outcomes data were collected using a test instrument comprising 30 multiple-choice questions. The data were analyzed using the Mann-Whitney statistical test at a significance level of 0.05. The analysis results revealed that the use of the problem-based learning model combined with mind mapping had a statistically significant impact on student learning outcomes, with a p-value less than 0.05 (0.000 < 0.05). Therefore, it can be concluded that the integration of mind mapping within the problem-based learning model has a positive influence on learning achievement. These findings suggest that this instructional approach is effective and can be implemented in lessons focused on ecosystem.